Effects of range‐wide variation in climate and isolation on floral traits and reproductive output of Clarkia pulchella. Issue 1 (15th September 2015) - Bontrager, Megan; Angert, Amy L.
Abstract : PREMISE OF THE STUDY: Plant mating systems and geographic range limits are conceptually linked by shared underlying drivers, including landscape‐level heterogeneity in climate and in species' abundance. Studies of how geography and climate interact to affect plant traits that influence mating system and population dynamics can lend insight to ecological and evolutionary processes shaping ranges. Here, we examined how spatiotemporal variation in climate affects reproductive output of a mixed‐mating annual, Clarkia pulchella . We also tested the effects of population isolation and climate on mating‐system‐related floral traits across the range. METHODS: We measured reproductive output and floral traits on herbarium specimens collected across the range of C. pulchella . We extracted climate data associated with specimens and derived a population isolation metric from a species distribution model. We then examined how predictors of reproductive output and floral traits vary among populations of increasing distance from the range center. Finally, we tested whether reproductive output and floral traits vary with increasing distance from the center of the range. KEY RESULTS: Reproductive output decreased as summer precipitation decreased, and low precipitation may contribute to limiting the southern and western range edges of C. pulchella . High spring and summer temperatures are correlated with low herkogamy, but these climatic factors show contrasting spatial patterns in different quadrants of the range. CONCLUSIONS: Limiting factors differ among different parts of the range. Due to the partial decoupling of geography and environment, examining relationships between climate, reproductive output, and mating‐system‐related floral traits reveals spatial patterns that might be missed when focusing solely on geographic position.